2014
DOI: 10.1016/j.physletb.2014.08.073
|View full text |Cite
|
Sign up to set email alerts
|

Decay law of relativistic particles: Quantum theory meets special relativity

Abstract: Late time properties of moving relativistic particles are studied. Within the proper relativistic treatment of the problem we find decay curves of such particles and we show that late time deviations of the survival probability of these particles from the exponential form of the decay law, that is the transition times region between exponential and non-exponential form of the survival amplitude, occur much earlier than it follows from the classical standard approach boiled down to replace time t by t/γL (where… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
88
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(98 citation statements)
references
References 31 publications
(78 reference statements)
7
88
0
Order By: Relevance
“…We also show that even in the case of a single component unstable system the decay curve has an oscillatory form with a smaller or a large amplitude of oscillations depending on the model considered. Next it will also be shown that the relativistic treatment of the problem within the Stefanovich-Shirokov theory [16,17] yields decay curves tending to zero as t → ∞ much slower than one would expect using classical time dilation relation which confirms and generalizes some conclusions drawn in [19]. Our results shows that conclusions relating to the quantum decay processes of moving particles based on the use of the classical physics time dilation relation need not be universally valid.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…We also show that even in the case of a single component unstable system the decay curve has an oscillatory form with a smaller or a large amplitude of oscillations depending on the model considered. Next it will also be shown that the relativistic treatment of the problem within the Stefanovich-Shirokov theory [16,17] yields decay curves tending to zero as t → ∞ much slower than one would expect using classical time dilation relation which confirms and generalizes some conclusions drawn in [19]. Our results shows that conclusions relating to the quantum decay processes of moving particles based on the use of the classical physics time dilation relation need not be universally valid.…”
Section: Introductionsupporting
confidence: 80%
“…The above derivation of the expression for a p (t) is similar to that of [19]. It is based on [37] and it is reproduced here for the convenience of readers.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
See 2 more Smart Citations
“…People are convinced that this equality being classical physics relation is valid also for any t in the case of quantum decay processes. The problem seems to be extremely important because from some theoretical studies it follows that in the case of quantum decay processes this relation is valid to a sufficient accuracy only for not more than a few lifetimes τ 0 = /Γ 0 [8,9,10]. All these problems require a deeper analysis, elements of which will be presented below.…”
Section: Introductionmentioning
confidence: 99%